A highly selective biosensor with nanomolar sensitivity based on cytokinin dehydrogenase - Tian, Faming; Greplová, Marta; Frébort, Ivo; Dale, Nicholas; Napier, Richard (PloS one, 2014)
We have developed a N6-dimethylallyladenine (cytokinin) dehydrogenase-based microbiosensor for real-time determination of the family of hormones known as cytokinins. Cytokinin dehydrogenase from Zea mays (ZmCKX1) was immobilised concurrently with electrodeposition of a silica gel film on the surface of a Pt microelectrode, which was further functionalized by free electron mediator 2,6-dichlorophenolindophenol (DCPIP) in supporting electrolyte to give a bioactive film capable of selective oxidative cleavage of the N6- side chain of cytokinins. The rapid electron shuffling between freely diffusible DCPIP and the FAD redox group in ZmCKX1 endowed the microbiosensor with a fast response time of less than 10 s. The immobilised ZmCKX1 retained a high affinity for its preferred substrate N6-(Δ2-isopentenyl) adenine (iP), and gave the miniaturized biosensor a large linear dynamic range from 10 nM to 10 µM, a detection limit of 3.9 nM and a high sensitivity to iP of 603.3 µAmM-1cm-2 (n = 4, R2 = 0.9999). Excellent selectivity was displayed for several other aliphatic cytokinins and their ribosides, including N6-(Δ2-isopentenyl) adenine, N6-(Δ2-isopentenyl) adenosine, cis-zeatin, trans-zeatin and trans-zeatin riboside. Aromatic cytokinins and metabolites such as cytokinin glucosides were generally poor substrates. The microbiosensors exhibited excellent stability in terms of pH and long-term storage and have been used successfully to determine low nanomolar cytokinin concentrations in tomato xylem sap exudates.
Keywords: Cytokinins; cytokininy; Isopentenyladenosine; enzymy imobilizované; isopentenyladenosin; limita detekce; Limit of Detection; biosenzitivní techniky; Biosensing Techniques; Enzymes, Immobilized; Zea mays; kukuřice setá; Oxidoreductases; oxidoreduktasy